Stability for the periodic Camassa-Holm equation - Lenells, Jonatan (MATHEMATICA SCANDINAVICA, 2005)
We use integrability to prove the stability of smooth periodic solutions of the Camassa-Holm equation. In particular, the smooth periodic traveling wave solutions are shown to be orbitally stable.